Combatting Helicobacter pylori with oral nanomedicines. Issue 48 (2nd December 2021) - Qin, Yuan; Lao, Yeh-Hsing; Wang, Haixia; Zhang, Jiabin; Yi, Ke; Chen, Zhuanggui; Han, Jing; Song, Wantong; Tao, Yu; Li, Mingqiang
Abstract : We review state-of-the-art oral nanomedicines for Helicobacter pylori eradication, from the mechanism and design to the resultant controllability and antimicrobial properties, and provide a deep insight into their challenges and future directions. Abstract : Helicobacter pylori ( H. pylori ) infection is considered to be the main cause of most digestive diseases, such as chronic active gastritis, gastroduodenal ulcers, or even gastric cancer. Oral medication is a transformative approach to treat H. pylori -induced infections. However, unlike intravenous administration, orally administrated drugs have to overcome various barriers before reaching the infected sites, which significantly limits the therapeutic efficacy. These challenges may be addressed by emerging nanomedicine that is equipped with nanotechnology approaches to enable efficient and effective targeted delivery of drugs. Herein, in this review, we first discuss the conventional therapy for the eradication of H. pylori . Through the introduction of the critical barriers of oral administration, the benefits of nanomedicine are highlighted. Recently-published examples of nanocarriers for combating H. pylori in terms of design, preparation, and antimicrobial mechanisms are then presented, followed by our perspective on potential future research directions of oral nanomedicines.